2017
DOI: 10.1007/s13205-017-0667-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in Costus pictus accessions based on RAPD and ISSR markers

Abstract: Costus pictus, belonging to the family Costaceae, is one of the valuable medicinal plants with its antidiabetic property. Despite ever-increasing demand from the pharmaceutical industry, this species is being less exploited at molecular level. Hence, an effort has been made in the present study to characterize the 15 accessions of C. pictus collected from different geographical regions of India through random amplified polymorphic DNA (RAPD) and inter-simple sequence repeats (ISSR) markers. A total of 25 RAPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Resolving powers in our study were in the range of 0.63-5.11 (average 2.98) for RAPD and ISSR 1.56-8.18 (average 4.10) per primer. According to Fang and Roose (1997) and Naik et al (2017), ISSR markers were found to be more effective in diversity study than RAPD markers. The present study clearly supports the view.…”
Section: Discussionmentioning
confidence: 99%
“…Resolving powers in our study were in the range of 0.63-5.11 (average 2.98) for RAPD and ISSR 1.56-8.18 (average 4.10) per primer. According to Fang and Roose (1997) and Naik et al (2017), ISSR markers were found to be more effective in diversity study than RAPD markers. The present study clearly supports the view.…”
Section: Discussionmentioning
confidence: 99%
“…In this system, PCR is performed on a short DNA sequence between two simple sequence repeat (SSR) sequences in genomic DNA with a single oligomerized nucleotide primer containing anchored 1-4 bases in the 3′ or 5′ end of the sequence, which are widely available and exhibits fast evolutionary rate (Esselman et al, 1999;Tanya et al, 2011;Hu et al, 2015). In addition, the features of long sequence and high annealing temperature ensure that ISSR-PCR would exhibit high stability and reproducibility (Nagaoka & Ogihara, 1997;Tsumura et al, 1996;Qian et al, 2001;Naik et al, 2017). Although ISSR is widely used in studies on various plants (Qian et al, 2001;Cao et al, 2006;Tanya et al, 2011), fungi (Menzies et al, 2003) and some insects Dutta et al, 2012;Barbosa et al, 2014), but it was less used on the study of termites (Long et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, low levels of polymorphism using both ISSR and RAPD markers were reported in Bruguirra gymnorrhiza and Heritiera fomes [30]. Most studies on wild plant populations have used the percentage of polymorphism as an indicator of genetic diversity [31]. However, [32] indicated that the percentage polymorphism is not a significant measure of genetic variation and that the parameter of genetic diversity (H) is more applicable.…”
Section: Population Genetic Parameters: Percentage Of Polymorphic Bmentioning
confidence: 99%